KERENTANAN DAN KAPASITAS RESPON MASYARAKAT KOTA PADANG TERHADAP BAHAYA TSUNAMI - Herryal Z. Anwar (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2012)
Potential risk of a disaster can not be separated from the potential natural hazards and the vulnerability of the people residing within a region. Experts estimate is that Padang City is one of the city in Indonesia are threatened by the danger of the tsunami. Both the City and the community have been aware of the potential tsunami waves that threaten the city of Padang. Recently, a number of tsunami hazard early warning sirens have been installed at several locations at Padang, which will warn the people if there are a tsunami threat. This study aims to understand and map response capacity the people of Padang toward tsunami early warning system and their vulnerability by using questionnaires and focus group discussion methods. The results of this study show that the category of people response is still not enough for tsunami warning to be more effective, although it should be emphasized that on the other hand the people vulnerability has been low enough, when the survey conducted in Padang City in between 2007 until 2009.